Measuring PERMA+4: validation of the German version of the Positive Functioning at Work Scale - Lorenz, Timo; Ho, Janika; Beyer, Marla; Hagitte, Leonie (Frontiers in Psychology, 2023)
This study investigates the association between the PERMA+4 model and psychological safety, while also examining the validation of the Positive Functioning at Work (PFW) scale in a German-speaking population. The study discovered strong association between PERMA+4 and psychological safety, which raises important questions and potential concerns regarding the jangle fallacy. Similar to the PERMA model, PERMA+4 should be considered a framework for attaining psychological safety. The German version of the PFW scale demonstrated satisfactory fit with the model, indicating its factorial validity. To gain insights into promoting workplace wellbeing, it is recommended to conduct longitudinal studies to determine whether psychological safety is a cause or result of PERMA+4. This study enhances our understanding of workplace wellbeing and emphasizes the association between PERMA+4 and psychological safety.